Constraining earthquake fault sources through the use of intensity data and seismic scenarios: application to the Betic Cordillera (South Spain) - De Pro-Díaz, Yolanda; Perea, Hector; Insua-Arévalo, Juan Miguel; Martínez-Díaz, José J.; Canora, Carolina (Frontiers in Earth Science, 2023)
Macroseismic observations can be useful to study pre-instrumental earthquakes when paleoseismological analysis are not viable for various reasons (e.g., erosion or lack of sedimentation). The analysis of the distribution of the macroseismic intensity data points and the reports about geological effects has been shown as a tool that may provide meaningful information to localize the fault source of a historical earthquake. Using this approach, we have studied two earthquakes in the Betic Cordillera (South Spain), the 1804 Dalías and the 1680 Málaga events, and we have used the 2011 Lorca earthquake as a test subject to calibrate the methodologies. During the calibration process, we also find the best performing combination of ground-motion models and ground-motion-to-intensity-conversion equations for generating seismic scenarios in this area. Even though the results for the Málaga earthquake were not conclusive, our methodology successfully identified the most likely source for the Dalías earthquake: a conjunct rupture of the Loma del Viento and Llano del Águila Faults.